(untitled) (Research, Society and Development, 2021)
This is an integrative review relating the effects of meditation in the brain and its possible use as preventive alternative medicine and an adjuvant in the psychiatric treatment. Studies have associated meditation and spirituality with increased life quality for being linked to emotional control and self-preservation behaviors, such as ethical practices, emotional regulation, attention improvement, stress and anxiety reduction and cognitive functions improvement in a general fashion, which is also evidenced by studies that analyzed morphological changes in correlated brain areas. This work proposes an integrative review in order to prove the hypothesis that meditation could be used as a practice in alternative and preventive medicine aiming to diminish the harmful effects of diseases and psychopathologies in general.